Rising anger over ‘lop-sided’ and ‘immoral’ US health funding pacts with African countries - Lay, Kat (The Guardian, 2026)
Zimbabwe refuses to sign agreement and Kenya faces a court case over data sharing as new aid deals come under scrutiny
Worldwide
Keywords: Africa; Aid; Aids and HIV; Data protection; Global development; Health; Medical research; Trump administration; US politics; World news; Zambia; Zimbabwe